System of Agencies and Institutions for Preventing and Counteracting Juvenile Delinquency (based on the materials of the Ukrainian provinces as part of the Russian Empire) (Law and Safety, 2020)
The author has studied the functional features and the legal status of the system of agencies and institutions for the prevention and counteraction to juvenile delinquency based on the materials of the Ukrainian provinces as part of the Russian Empire.The author has carried out analysis and has singled out specific features of the tasks and competences of certain agencies and institutions, which activity was in one way or another related to the counteraction to juvenile delinquency. Special attention in the chosen context has been paid to the Ministry of Internal Affairs, as well as to the functioning of charitable institutions and organizations.The emphasis has been placed on the fact that the activities of the Ministry of Internal Affairs were related to the development and adoption of various regulatory acts (instructions, circulars, decrees, orders) aimed at counteracting and preventing offenses committed by juveniles, as well as in the field of custody of children and adolescents, including in the field of combating begging, vagrancy and prostitution of minors as the most common socially dangerous phenomena.The participation and role of charitable institutions and organizations in the period of the Russian Empire in counteracting and preventing juvenile delinquency have been studied. It has been proved that private charity of non-governmental (informal) public organizations and individuals was very common on the cusp of the XIX and the XX centuries, and their activities covered almost all areas of social assistance to children and adolescents in need. Assistance and support was provided to a rather wide range of persons, mainly to create conditions that prevent the commission of juvenile delinquency and their further criminalization.
Keywords: minors; juvenile offenders; criminal liability; crime; combating crime; subject of a crime; crime prevention